2016
DOI: 10.1128/jcm.01298-15
|View full text |Cite
|
Sign up to set email alerts
|

Triton Hodge Test: Improved Protocol for Modified Hodge Test for Enhanced Detection of NDM and Other Carbapenemase Producers

Abstract: Accurate detection of carbapenemase-producing Gram-negative bacilli is of utmost importance for the control of nosocomial spread and the initiation of appropriate antimicrobial therapy. The modified Hodge test (MHT), a carbapenem inactivation assay, has shown poor sensitivity in detecting the worldwide spread of New Delhi metallo-␤-lactamase (NDM). Recent studies demonstrated that NDM is a lipoprotein anchored to the outer membrane in Gram-negative bacteria, unlike all other known carbapenemases. Here we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 27 publications
1
60
0
3
Order By: Relevance
“…Also, our results revealed 2 strains of P. stuartii, 1 strain of S. marcescens and 1 isolate of K. pneumoniae harbouring gene bla NDM , which were negative for the MHT with both meropenem and ertapenem disks. Similar reports recognized the MHT unsatisfying performance in the detection of NDM-carriers, with sensitivity below 50% (2,8,14,21,22). Recent studies demonstrated that NDM is a lipoprotein anchored to the outer membrane in Gram-negative bacteria, unlike all other known carbapenemases (21).…”
Section: No Of Susceptible and Intermediate Susceptible Isolates Bymentioning
confidence: 74%
“…Also, our results revealed 2 strains of P. stuartii, 1 strain of S. marcescens and 1 isolate of K. pneumoniae harbouring gene bla NDM , which were negative for the MHT with both meropenem and ertapenem disks. Similar reports recognized the MHT unsatisfying performance in the detection of NDM-carriers, with sensitivity below 50% (2,8,14,21,22). Recent studies demonstrated that NDM is a lipoprotein anchored to the outer membrane in Gram-negative bacteria, unlike all other known carbapenemases (21).…”
Section: No Of Susceptible and Intermediate Susceptible Isolates Bymentioning
confidence: 74%
“…However, the MHT has poor sensitivity for class B carbapenemases (sensitivity <50 %) which is marginally improved by addition of ZnSO 4 (sensitivity 87%) [Girlich 2012]. As reported in Argentina in 2016, addition of 0.2% Triton X-100 [vol/vol] to Mueller Hinton Agar plates improved sensitivity (97–100%) for detecting class B carbapenemase expressing CPE [Pasteran 2016]. The proposed mechanism relies on the anionic detergent disturbing the hydrophobic interactions between the lipoprotein carbapenemases and the outer membrane [Gonzalez 2016, Pasteran 2016].…”
Section: Detectionmentioning
confidence: 99%
“…The genes coding for these enzymes were cloned with their peptide leaders in a plasmid designed for the controlled expression of MBLs . This system allows the induction of MBL expression with IPTG, in such a way that the enzymes are expressed at levels similar to those found in clinical strains with their native promoter, avoiding artifacts due to overexpression …”
Section: Resultsmentioning
confidence: 99%
“…20 This system allows the induction of MBL expression with IPTG, in such a way that the enzymes are expressed at levels similar to those found in clinical strains with their native promoter, avoiding artifacts due to overexpression. 20,22 F I G U R E 1 Localization of NDM-1, NDM-1 C26A and NDM-8 in the periplasm of Escherichia coli. The New Delhi Metallo-β-lactamase (NDM-1) has a lipobox sequence in its N-terminal, which is recognized by the lipidation machinery of Gram-negative bacteria.…”
Section: Spheroplasts As a System To Characterize Lipidated Proteinsmentioning
confidence: 99%